2011
DOI: 10.1128/aac.00590-11
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Susceptibility to Azithromycin among Salmonella enterica Isolates from the United States

Abstract: Due to emerging resistance to traditional antimicrobial agents, such as ampicillin, trimethoprim-sulfamethoxazole, and chloramphenicol, azithromycin is increasingly used for the treatment of invasive Salmonella infections. In the present study, 696 isolates of non-Typhi Salmonella collected from humans, food animals, and retail meats in the United States were investigated for antimicrobial susceptibility to azithromycin. Seventy-two Salmonella enterica serotype Typhi isolates from humans were also tested. For … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
83
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(86 citation statements)
references
References 31 publications
1
83
2
Order By: Relevance
“…Indian studies have reported higher MIC90 for azithromycin in S. Typhi and S. Paratyphi A (24 μg/mL) [10,29] compared to Western studies (MIC90 8 μg/mL, MIC range 4-16 μg/mL) [30,31]. In one Indian study, taking a MIC interpretive breakpoint of >16 μg/mL, 36 (33.6%) of Salmonella isolates were azithromycin-resistant, while clinical non-response to azithromycin therapy was observed in 19 patients (both azithromycin susceptible and resistant isolates with MIC range 6-64 μg/mL, MIC90 24 μg/mL were included) [10].…”
Section: Discussionmentioning
confidence: 93%
“…Indian studies have reported higher MIC90 for azithromycin in S. Typhi and S. Paratyphi A (24 μg/mL) [10,29] compared to Western studies (MIC90 8 μg/mL, MIC range 4-16 μg/mL) [30,31]. In one Indian study, taking a MIC interpretive breakpoint of >16 μg/mL, 36 (33.6%) of Salmonella isolates were azithromycin-resistant, while clinical non-response to azithromycin therapy was observed in 19 patients (both azithromycin susceptible and resistant isolates with MIC range 6-64 μg/mL, MIC90 24 μg/mL were included) [10].…”
Section: Discussionmentioning
confidence: 93%
“…Occasional patients in these studies have demonstrated a slow clearance of bacteremia. Several studies have reported azithromycin MIC distributions for typhoidal and nontyphoidal Salmonella strains (501,511,(562)(563)(564)(565). These studies have led to a suggested epidemiologic MIC cutoff value of Յ16 g/ml for wild-type strains (566,567) 570).…”
Section: Azithromycinmentioning
confidence: 99%
“…for azithromycin (Sj€ olund-Karlsson et al, 2011). Nonetheless, to date no clinical resistance breakpoint has been established for the members of the Enterobacteriaceae family by either CLSI or EUCAST (CLSI, 2013;EUCAST, 2015).…”
Section: Mechanisms Of Resistancementioning
confidence: 99%